2011
DOI: 10.19182/bft2011.308.a20470
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité spatio-temporelle des insectes mangeurs de fruits utilisés comme bioindicateurs en Afrique de l'ouest

Abstract: Les insectes mangeurs de fruits se sont récemment avérés de très bons bioindicateurs de santé des écosystèmes savanicoles d'Afrique de l'Ouest. Au Burkina Faso, la fragmentation grandissante des paysages dans diverses régions rend le développement de ce genre d'outils de suivi particulièrement utile. Cette étude a été réalisée pour mesurer la variabilité spatio-temporelle des densités apparentes d'insectes, de la famille des Nymphalidae et des Cetoniinae, attirés par des pièges appâtés de bananes fermentées, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Their characteristics include taxonomical and ecological diversity, ecological fidelity, sedentary (species with short dispersal range), endemicity (non-invasive species), taxonomical knowledge and ease of identification, abundance and ease of monitoring, indication of other species and specific resources, temporal and spatial fluctuations and predictable, rapid, sensitive, and a linear response to disturbance that is easy to analyze 21,22 . The seasonal variation of the apparent densities of these ecological indicators is the only limitation and therefore, the monitoring must be done during the same period of the year 23 . For this study, the traps were deployed for eight consecutive years in October-November, a period that coincides with the end of the rainy season – beginning of the cold dry season and is the period of their highest diversity and density.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their characteristics include taxonomical and ecological diversity, ecological fidelity, sedentary (species with short dispersal range), endemicity (non-invasive species), taxonomical knowledge and ease of identification, abundance and ease of monitoring, indication of other species and specific resources, temporal and spatial fluctuations and predictable, rapid, sensitive, and a linear response to disturbance that is easy to analyze 21,22 . The seasonal variation of the apparent densities of these ecological indicators is the only limitation and therefore, the monitoring must be done during the same period of the year 23 . For this study, the traps were deployed for eight consecutive years in October-November, a period that coincides with the end of the rainy season – beginning of the cold dry season and is the period of their highest diversity and density.…”
Section: Resultsmentioning
confidence: 99%
“…The scores considered the following characteristics of these groups:both insect families are taxonomically well-known and ecologically highly diversified 38–41 ;the species selected as indicators are widely distributed in open savannah from the Guinean to the Sahelian regions in Africa and do not display high ecological fidelity;the mobility of both insect groups do not affect their indicator value since their densities drop or increase very quickly with distance depending on human activity;the selected species are generally caught in high densities and capture scores allow strong statistical analyses, which lead us to switch three of Brown’s criteria (1991) to the maximum level for bait-attracted Nymphalinae in past studies (abundant, non-furtive, easy to find in the field, damped fluctuations, easy to obtain large random samples of species and variation). Seasonal variations, previously described in Burkina Faso 23 , were taken into consideration (see below) and vertical variations are not likely in savannah ecosystems, where the canopy is not continuous and the trees generally small (<10 m).the importance of both groups in the ecosystem is probably modest, although the Cetoniinae larvae are saprophytic and play a role in the recycling of organic matter 42 ;we previously demonstrated that the response of the selected species to ecosystem disturbance is sensitive and analysable 21 . However, the response to disturbance is not linear in the Cetoniinae subfamily, actually favored by a slight disturbance;finally, a linear relationship was found between plant species richness and the apparent densities of the most abundant species, which were also correlated together, although belonging to different families.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations